RNA secondary structure regulates the translation of sxy and competence development in Haemophilus influenzae - Cameron, Andrew D.S. (Oxford University Press, 2008)
The sxy (tfoX) gene product is the central regulator of DNA uptake by naturally competent γ-proteobacteria such as Haemophilus influenzae, Vibrio cholerae and probably Escherichia coli. However, the mechanisms regulating sxy gene expression are not understood despite being key to understanding the physiological role of DNA uptake. We have isolated mutations in H. influenzae sxy that greatly elevate translation and thus cause competence to develop in otherwise non-inducing conditions (hypercompetence). In vitro nuclease analysis confirmed the existence of an extensive secondary structure at the 5′ end of sxy mRNA that sequesters the ribosome-binding site and start codon in a stem-loop. All of the hypercompetence mutations reduced mRNA base pairing, and one was shown to cause a global destabilization that increased translational efficiency. Conversely, mutations engineered to add mRNA base pairs strengthened the secondary structure, resulting in reduced translational efficiency and greatly reduced competence for genetic transformation. Transfer of wild-type cells to starvation medium improved translational efficiency of sxy while independently triggering the sugar starvation regulator (CRP) to stimulate transcription at the sxy promoter. Thus, mRNA secondary structure is responsive to conditions where DNA uptake will be favorable, and transcription of sxy is simultaneously enhanced if CRP activation signals that energy supplies are limited.